Effects of the micro surface texturing in lubricated non-conformal point contacts. (November 2018) - Joshi, G.S.; Putignano, C.; Gaudiuso, C.; Stark, T.; Kiedrowski, T.; Ancona, A.; Carbone, G.
Abstract: This paper presents an experimental study on the effects of micro-textured surfaces on lubricated non-conformal point contacts. Thus, we focus on a regime poorly investigated in literature, where the contact area and the micro-holes have a comparable size. Tribological characterization are performed on three geometrical patterns, which are textured on stainless steel polished surfaces. Experiments are carried out on a rheometer, where a steel ball slides against the surface of the samples. These samples are tested with two different viscosities of the PAO (Poly-Alpha-Olefin)as a lubricant. Results show the change in the friction with respect to the sliding velocity under different lubrication regimes due to the stress, void ratio and two different kinematic viscosities of PAO. In particular, we show that, depending on the void ratio, a significant friction reduction or, on the contrary, a deterioration of the frictional performances can affect the boundary and mixed lubrication regimes. This is due to the simultaneous occurrence of two competing effects. One is related to the stress intensification, due to the presence of the micro-hole edges on the contact topography, which leads to a consequent increase in wear and friction. On the other hand, micro-texture may play a positive role in the friction optimization given the possibility, offered by the micro-holes, to entrap wear debris and, then, to preverse a smoother interface between the contacting pairs. Highlights: Tribological Investigation of the non-conformal point contacts where contact area and micro-holes have comparable size. The void ratio influences friction reduction or deterioration of the frictional performances in different lubrication regimes. Stress intensity increase due to micro-hole edges on the contact topography which causes high wear and friction. Micro-texture helps in reducing friction by entrapping wear debris thus forming a smoother interface in the tribo-pair. High void ratio can be useful to enhance the entrapping effect and decrease the friction.